2010
DOI: 10.1051/0004-6361/200913590
|View full text |Cite
|
Sign up to set email alerts
|

The complex structure of the disk around HD 100546

Abstract: Context. Disclosing the structure of disks surrounding Herbig AeBe stars is important to expand our understanding of the formation and early evolution of stars and planets. The first astronomical units of these disks in particular, because they are hot, dense, and subject to intense radiation field, hold critical clues to accretion and ejection processes, as well as planet formation in environment different than what prevailed around our own early Sun. Aims. We aim at revealing the sub-AU disk structure around… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
173
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 108 publications
(185 citation statements)
references
References 31 publications
(65 reference statements)
12
173
0
Order By: Relevance
“…In such a model, the NIR emission is dominated by the puffed-up inner rim at the dust sublimation radius, and the region of the disk behind the rim is colder owing to shadowing effects, which can lead to a gap in the observed intensity distribution. A gap phenomenon was also reported for other Herbig stars (e.g., Benisty et al 2010;Tatulli et al 2011). While the NIR emission of the disk is dominated exclusively by the inner ring (presumably the puffed-up rim), the MIR emission has a bimodal distribution, with ∼20% of the emission originating from the inner ring, and the rest from the (Monnier & MillanGabet 2002).…”
Section: Discussionsupporting
confidence: 63%
“…In such a model, the NIR emission is dominated by the puffed-up inner rim at the dust sublimation radius, and the region of the disk behind the rim is colder owing to shadowing effects, which can lead to a gap in the observed intensity distribution. A gap phenomenon was also reported for other Herbig stars (e.g., Benisty et al 2010;Tatulli et al 2011). While the NIR emission of the disk is dominated exclusively by the inner ring (presumably the puffed-up rim), the MIR emission has a bimodal distribution, with ∼20% of the emission originating from the inner ring, and the rest from the (Monnier & MillanGabet 2002).…”
Section: Discussionsupporting
confidence: 63%
“…However, for an optically thick scattering surface the difference in the radial profiles can be explained with differences in the disk geometry, i.e., stronger disk flaring in HD 97048. And indeed, Benisty et al (2010) A direct comparison between the H-band surface brightness of the two disks reveals that at 60 AU both disks have roughly the same brightness with 13.5 mag/arcsec 2 . At smaller projected separations HD 100546 appears brighter, while at larger separations HD 97048 is brighter.…”
Section: Comparison To Hd 100546mentioning
confidence: 88%
“…Based on the mid-to near-IR excess ratio, Bouwman et al (2003) suggested an inner cavity in the disk. Later observations confirmed this gap (e.g., Grady et al 2005;Benisty et al 2010). This remarkable feature and the longevity of the HD 100546 disk may point to a young planet in the inner 10 AU, making it a prime target for detailed studies.…”
Section: Introductionmentioning
confidence: 84%